Heterogeneous Spillover Effects of Outward FDI on Global Value Chain Participation - Wang, Yanfang; Chen, Shumei (Panoeconomicus, 2020)
This study delves into the effects of outward foreign direct investment (FDI) on global value chain (GVC) participation from 2000 to 2014. The utilization of traditional panel models, the spatial Durbin model (SDM), and the threshold model provides a comprehensive understanding of the heterogeneous spillover effects of outward FDI. The results show that increased outward FDI not only facilitates the GVC participation of parent countries but also has a profound impact on that of other countries. The spillover effects of outward FDI play a vital role in the GVC participation of low total factor productivity (TFP) countries. However, for developed countries with high TFP levels, outward FDI has positive impacts on deep GVC participation while not influencing shallow participation. These findings serve as an extension to the relevant theories and suggest a way for developing countries to capture gains from outward FDI and participate further in GVCs. Key words: Outward FDI, GVC participation, SDM, Threshold model. JEL: F15, F23.